Improved power system state estimation based on rectangular coordinates - Rakpenthai C. (2014)
This paper presents a new state estimation method based on the equivalent current measurement model and rectangular coordinate state variables. The bus voltage phasors in rectangular form are considered as the estimated states. Voltage magnitude, power measurements and estimated voltage buses are employed to find equivalent current phasor measurements. With this formulation, the measurement equation can be formulated as a linear-like system and the solution can be obtained by iterative computation using a constant gain matrix. Numerical simulations on the IEEE 14, 30, and 57-bus systems based on the proposed formulation have been performed. The results are then compared with the conventional method based on polar form of state variables. It is found that the proposed method requires lesser computational time, especially for a large power system. © American Institute of Physics.